Employment Variability Under Different Managerial Compensation Systems - Gerhart, Barry; Trevor, Charlie O. (Academy of Management Journal, 1996)
Variability in employment levels, particularly when resulting from downsizing and layoffs, has considerable consequences for employees and organizations. Applying strategic compensation and agency theory principles to multiple years of employment, financial performance, and managerial compensation data on 152 organizations, we found that compensation design was related to employment variability through two avenues. First, organizations relying more heavily on long-term compensation incentives for managers exhibited less employment variability. Second, when groups of employees were covered by variable pay plans, their employment variability was lower.